Presence of tumor cells in intra-operative blood salvage autotransfusion samples from hepatocellular carcinoma liver transplantation: analysis using highly sensitive microfluidics technology. Issue 11 (November 2021) - Tan, Jarrod K.H.; Menon, Nishanth V.; Tan, Pei Shan; Pan, Terry L.T.; Bonney, Glenn K.; Shridhar, Iyer G.; Madhavan, Krishnakumar; Lim, Chwee Teck; Kow, Alfred W.C.
Abstract: Background: The application of intra-operative blood salvage autotransfusion(IBSA) in liver transplantation(LT) for hepatocellular carcinoma(HCC) remains controversial due to the theoretical risk of tumour cell(TC) reintroduction. Current studies evaluating for presence of TC are limited by suboptimal detection techniques. This study aims to analyze the presence of TC in HCC LT autologous blood using microfluidics technology. Methods: A prospective study of HCC patients who underwent LT from February 2018–April 2019 was conducted. Blood samples were collected peri-operatively. TCs were isolated using microfluidics technology and stained with antibody cocktails for confirmation. Results: A total of 15 HCC LT patients were recruited. All recipients had tumour characteristics within the University of California, San Francisco(UCSF) criteria pre-operatively. TC was detected in all of the autologous blood samples collected from the surgical field. After IOCS wash, five patients had no detectable TC, while 10 patients had detectable TC; of these two remained positive for TC after Leukocyte Depletion Filter(LDF) filtration. Conclusion: The risk of tumour cell reintroduction using IBSA in HCC LT patients can be reduced with a single LDF. Future studies should evaluate the proliferation capacity and tumorigenicity of HCC TC in IBSA samples, and the effects of TC reintroduction in patients with pre-existing HCC TCs.